Corporate takeover and market efficiency The Malaysian Experience - Fauzias Mat Noor, (Penerbit Universiti Kebangsaan Malaysia, 1992)
The purpose of this study is to test the efficiency of the Malaysian stock market reaction with regard to acquisition announcement. The result on insignificant cumulative average residuals from day -1 to + I for bidders indicates that the Kuala Lumpur Stock Exchange market is reasonably efficient in its response to takeover bids that are subsequently successful. But, with the bidder's highest cumulative • average residuals reported on the announcement date, and declines significantly immediately after the announcement indicates that the Kuala Lumpur Stock Exchange is reasonably efficient in terms of the speed of information, hut it does not accurately reflect the true implication on the value of the shares. This may also suggest that the bidder has over estimated the value of the target which may result in paying too much for its assets. The increase in share prices prior to the announcement may be due to the information leakage to the market or to buying support by the bidder which forcing the prices up before the announcement.